The Values Of Gadang House In Minangkabau Society Through Symbolic Analysis - Abdul Rokhmat Sairah, Misnal Munir, Rizal Mustansyir, Supartiningsih, (Opción, 2019)
The aim of the study is to investigate the values of Gadang house in Minangkabau society through symbolic analysis via comparative qualitative research methods. As a result, human rights or demands and needs for survival in fact are related to personal factors, groups of people, the community (customs, religion, politics, etc.). In conclusion, there are effects of Minangkabau community cultural environment on the perception formation of community member about the environment. This perception shapes on the community member behaviour in managing the natural environment